Modelagem do processo de projeto de produto de uma empresa de estruturas metálicas para suporte de módulos fotovoltaicos - Pereira, Felipe Ugalde (2022)
Renewable energy is of great importance now a days in the world, as well as the reduction of emission of greenhouse gases and CO2 into the atmosphere. The use of photovoltaic modules is directly linked to this behavior change as the alteration of the energetic matrix proposed in Brazil. The country has great potential for generating energy through the incidence of solar radiation, since it has an average of 1,600 kWh/kWp, when compared to other countries, such as Germany, which has an average of 1,020 kWh/kWp. Given the importance of the topic and the indicative of growth in the production of metallic support structures for photovoltaic modules in the Brazilian market, the main objective of this study was to model the process of product design currently developed by a small company, in the state of Rio Grande do Sul, now active in this sector. To achieve this purpose, a case study research was carried out with the selected company. The collected data were tabulated in electronic spreadsheets and presented through graphics, flowcharts and associated descriptions. The main result obtained was the establishment of a particular formalized model of the process practiced by the company. From the particular model, it was possible to evaluate it in terms of its completeness in relation to the prescriptions of the reference model for the Process of Development of Industrial Products – PRODIP. Seeking to establish an equivalence between the particular model and the reference model, it was found that the process currently practiced by the company has the same number of phases (eight), however, when compared to the number of activities carried out to develop the product itself, the process fewer than what is prescribed by the PRODIP model. Regarding to the product development process formalization, the company has 37.5% and to the project management 28.6% compliance with the proposed requirements. In this way, it is possible to identify the weaknesses of the current process and, on these, apply the principles of continuous improvement to build a more complete process, with the implementation of new intermediate activities, allowing it to have a greater alignment and approximation between the strategic planning of the company and the tasks of product design, bringing greater competitiveness to the company in a rapidly expanding market.